2006
DOI: 10.4161/cbt.5.5.2597
|View full text |Cite
|
Sign up to set email alerts
|

Tumoral expression of BRCA1, Estrogen receptor alpha and ID4 protein in patients with sporadic breast cancer

Abstract: Introduction: BRCA1 expression is downregulated in a third of sporadic breast cancers (SBC). Most of the tumors in which BRCA1 function is diminished do not express estrogen receptor alpha (ER). Recent studies suggest that the inhibitor of DNA binding (ID)-4 could participate in the hormonal regulation of BRCA1 expression.Objective: To study the relationship between tumoral expression of BRCA1, ER and ID4 in SBCs.Patients and methods: Forty patients with pathologic confirmation of SBC were included in this stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 42 publications
2
37
1
3
Order By: Relevance
“…In the present study, the expression of Id-4 protein increased in breast cancer in comparison with the adjacent breast tissues, suggesting that Id-4 protein may play a positive role in carcinogenesis of human breast cancer, consistent with the study by Shan et al (20). Moreover, expression of Id-4 protein was negatively correlated with TNM stage and survival time, suggesting that decreased Id-4 expression may promote human breast cancer progression, which is different from the results in rats that Id-4 protein positively correlated with invasive ability of a mouse breast cancer cell line (21), and this result is also different from the results that Id-4 protein was a crucial gene regulating BRCA1 expression and might therefore be important for BRCA1 regulatory pathway involved in the pathogenesis of sporadic breast cancer (13,22). This illustrated that future work is required to elucidate the function of Id-4 protein in breast cancer.…”
Section: ------------------------------------------------------------contrasting
confidence: 97%
See 1 more Smart Citation
“…In the present study, the expression of Id-4 protein increased in breast cancer in comparison with the adjacent breast tissues, suggesting that Id-4 protein may play a positive role in carcinogenesis of human breast cancer, consistent with the study by Shan et al (20). Moreover, expression of Id-4 protein was negatively correlated with TNM stage and survival time, suggesting that decreased Id-4 expression may promote human breast cancer progression, which is different from the results in rats that Id-4 protein positively correlated with invasive ability of a mouse breast cancer cell line (21), and this result is also different from the results that Id-4 protein was a crucial gene regulating BRCA1 expression and might therefore be important for BRCA1 regulatory pathway involved in the pathogenesis of sporadic breast cancer (13,22). This illustrated that future work is required to elucidate the function of Id-4 protein in breast cancer.…”
Section: ------------------------------------------------------------contrasting
confidence: 97%
“…Id-1 protein was highly expressed in infiltrating human breast cancer specimens with a significant correlation with tumor angiogenesis (11), while high cytoplasmic level of Id-2 reflects a favorable prognosis in patients with primary breast cancer and reduces invasiveness of breast cancer cells (12). Id-4 is highly expressed in normal human mammary epithelium and ER-negative carcinomas, but is suppressed in ER-positive breast carcinomas and preneoplastic lesions (13). Hypermethylation of Id-4, which leads to reduced gene expression, is significantly associated with the risk of regional lymph node metastasis of human breast cancer (14).…”
Section: Introductionmentioning
confidence: 99%
“…Beger and coworkers (2001) subsequently characterised the regulators of BRCA1 gene expression and identified ID4 as an upstream regulator of the BRCA1 promoter using an inverse genomics approach in luminal breast cancer cell lines. However, our research, and that from other laboratories, has shown exclusive ID4 protein expression in the ERα-negative subtypes of breast cancer, particularly BLBC where it is believed ID4 plays a crucial role in aetiology of this disease (de Candia et al 2006, Roldán et al 2006, Wen et al 2012, Best et al 2014, Junankar et al 2015. Importantly, the inhibitory effect of ID4 on BRCA1 has since been confirmed in ERα-negative breast cancer cell lines (Crippa et al 2014).…”
Section: Id4 and Brca1 In Blbcmentioning
confidence: 48%
“…BRCA1, the breast and ovarian cancer susceptibility gene, is responsible for the majority of hereditary breast cancer cases ( (Lakhani et al 2005, Turner et al 2007) and reviewed in Mavaddat et al 2010). BRCA1 and ERα mRNA expression have been shown to correlate in sporadic breast cancers (Roldán et al 2006), while ID4 is negatively correlated to both BRCA1 and ERα (Roldán et al 2006, Thike et al 2015. This phenomenon has been suggested to occur through ERα inhibition of ID4 in a luminal breast cancer cell line (Beger et al 2001).…”
Section: Id4 Erα and Brca1 In Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation